A Rare Case of Spontaneous Rupture of a Renal Angiomyolipoma in a Post-Partum Patient - Birajdar, Dr. Pushkraj Baswant; Thakur, Dr. Sanjeev S.; Patil, Dr. Shalil H. (International Journal of Innovative Research in Medical Science, 2017)
A 26 year female, postoperative cesarean section day 2, presented with sudden onset pain in left loin and abdominal distension with hematuria referred from peripheral rural hospital with unstable hemodynamics. After resuscitation, evaluated with CT scan Abdomen Pelvis (P+C) and found to have left sided large renal ruptured hemorrhagic mass with gross hemoperitoneum. Emergency Exploratory Laparotomy done and left sided renal hemorrhagic mass removed with nephrectomy. Post-op period uneventful. Histopathological study has diagnosed it as Renal Angiomyolipoma which is a rare case to present like this in postpartum female.